KEBIJAKAN PENGEMBANGAN PARIWISATA SEHAT MELALUI HASIL SINTESIS CLUSTER INDIKATOR POKOK SARANA - Nur Anim Jauhariyah; Nihayatul Wafiroh (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
Tourism is one sector that can contribute to certain regional incomes. Healthy tourism must be accompanied by facilities that support tourist needs. This research aims to analyze the priorities for healthy tourism development based on the main indicators of facilities in Banyuwangi Regency. The research method uses quantitative research by distributing questionnaires to expert respondents. Analysis uses an Analytic Network Process (ANP). The results of the research show that the value of Kendall's coefficient of concordance W (rater agreement) is 0.85. The diversity of scores given by each respondent contributed to the rater agreement figure of 85%. This shows that the level of agreement of respondents regarding the priority order in the tourism facilities sub-criteria is high, referring to facilities as an important indicator in serving tourists. Keywords: Tourism, Facilities, Analytical Network Process (ANP). Abstrak: Pariwisata menjadi salah satu sektor yang dapat memberikan kontribusi untuk pendapatan daerah tertentu. Pariwisata yang sehat harus disertai dengan sarana yang mendukung kebutuhan wisatawan. Tujuan penelitian ini adalah menganalisis prioritas pengembangan pariwisata sehat berdasarkan indikator pokok sarana di Kabupaten Banyuwangi. Metode penelitian menggunakan penelitian kuantitatif dengan penyebaran kuesioner ke responden expert. Analisis menggunakan Analytic Network Process (ANP). Hasil penelitian menunjukkan bahwa nilai kendall’s coefficient of concordance W (rater agreement) sebesar 0,85. Keragaman nilai yang diberikan oleh masing-masing responden turut menyumbang perolehan angka rater agreement sebesar 85% hal ini menunjukkan bahwa tingkat kesepakatan responden atas urutan prioritis pada sub kriteria sarana pariwisata adalah tinggi, mengacu sarana merupakan salah satu indikator penting dalam melayani wisatawan. Kata Kunci: Pariwisata, Sarana, Analytic Network Process (ANP) References Ahmad Munib Syafa’at, & Nur Anim Jauhariyah. (2023). Analisis Faktor Pemberdayaan Ekonomi Masyarakat Sekitar Pesantren. ICO EDUSHA, 3(1), 71–80. Retrieved from https://prosiding.stainim.ac.id/index.php/prd/article/view/227. BPS Kabupaten Banyuwangi. 2019. Banyuwangi Dalam Angka 2019. BPS Kabupaten Banyuwangi. Creswell, J. 2003. Research design: Qualitative, quantitative and mixed methods approaches (2nd ed.). Thousand Oaks, CA: SAGE Publications. Dunn, W.H. 2000. Pengantar Analisis Kebijakan Publik. Yogyakarta: Gajah Mada University Press Juanda, Bambang. 2009. Metodologi Penelitian Ekonomi & Bisnis. Bogor: Ipb Press. Hamilton, W. H. (1919). The Institutional Approach To Economic Theory. The American Economic Review, 9(1), 309–318. Hogwood, Brian W., Gunn, Lewis A. 1984. Policy Analysis For The Real. World. Oxford University Jauhariyah, Nur Anim; Syafa’at, Ahmad Munib; Khusnudin, Iman. Analisis Potret Pertumbuhan Kunjungan Wisatawan Terhadap Pendapatan Asli Daerah Di Kabupaten Banyuwangi. Sifebri's, [S.L.], V. 1, N. 1, P. 156-162, Aug. 2023. Issn 3025-3489. Available At: <https://Unars.Ac.Id/Ojs/Index.Php/Sifebri/Article/View/3320> Jauhariyah, Nur Anim; Syafa’at, Ahmad Munib; Khusnudin, Iman. Analisis Potret Pertumbuhan Kunjungan Wisatawan Terhadap Pendapatan Asli Daerah Di Kabupaten Banyuwangi. Sifebri's, [S.L.], V. 1, N. 1, P. 156-162, Aug. 2023. Issn 3025-3489. Available At: <https://Unars.Ac.Id/Ojs/Index.Php/Sifebri/Article/View/3320> Jauhariyah. N. A., & MahmudahM. (2023). Empowering Students In Improving The Economy Of Pesantren Through Sustainable Waste Management. Proceedings of Annual Conference on Community Engagement, 4, 233-240. Retrieved from https://proceedings.uinsby.ac.id/index.php/ACCE/article/view/1520. Jauhariyah, Nur Anim, Susanti, Nawal Ika, Indana, Fatiha. (2023). Pengembangan Pemberdayaan Ekonomi Pesantren Melalui Pengelolaan Sampah Secara Berkelanjutan. LOYALITAS, Jurnal Pengabdian Kepada Masyarakat, v. 6, n. 2, p. 116-127. < https://ejournal.iaida.ac.id/index.php/loyal/article/view/2250> Keynes, J. M. (1973a). The General Theory Of Employment, Interest And Money. In Education. Cambridge University Press Cambridge, Keynes, John Maynard. 1936. The General Theory Of Employment, Interest, And Money. Diakses Di Https://Www.Files.Ethz.Ch/Isn/125515/1366_Keynestheoryofemployment.Pdf Keynes, John Maynard. 1936. The General Theory Of Employment, Interest, And Money. Diakses Di Https://Www.Files.Ethz.Ch/Isn/125515/1366_Keynestheoryofemployment.Pdf Klein, M. 2005. Survival Analysis A Self Learning Text. Springer-. Verlag: New York. Moffat, Mike. 2019. The Government's Role In The Economy. Agustus 22. Thoughtco.Com/The-Governments-Role-In-The-Economy-1147544. Peraturan Bersama Mendagri Dan Menkes No. 34 Tahun 2005 Dan No. 1138/Menkes/Pb/Viii/2005 Tanggal 3 Agustus 2005 Tentang Kabupaten/Kota Sehat. Priyono, & Ismail, Z. (2012). Teori Ekonomi Solow. Dharma Ilmu. Rutherford, M. (2001). Institutional Economics: Then And Now. Journal Of Economic Perspectives, 15(3), 173–194. Https://Doi.Org/10.1257/Jep.15.3.173. Saaty, L. Thomas And Luis G. Vargas. 2012. Models, Methods, Concepts& Applications Of The Analytic Hierarchy Process. Springer New York Heidelberg Dordrecht London. Doi 10.1007/978-1-4614-3597-6 Spithoven, A. (2017). The Role Of Governments In Aligning Functional Income Distribution With Full Employment. Journal Of Economic Issues, 51(3), 688–697. Https://Doi.Org/10.1080/00213624.2017.1359035. Todaro, Michael P. Dan Stephen C. Smith. 2011. Pembangunan Ekonomi Jilid 1 Edisi Kesebelas. Jakarta: Penerbit Erlangga Tulkens, H. (2006). Public Goods , Environmental Externalities. Springer Science+ Business Media New York